A sociophonetic account of gradient /z/ devoicing among Chicanx high schoolers. (July 2022) - Holliday, Nicole; Brogan, Franny D.
Abstract: This paper examines final /z/ devoicing among Chicanx teens in Southern California to investigate the degree to which devoiced final /z/ neutralizes with final /s/ in this dialect. Results indicate on the one hand that devoiced /z/ remains distinct from /s/: as expected, devoiced /z/ is significantly less voiceless than /s/ and has a significantly lower center of gravity (COG). However, unexpectedly, devoiced /z/ has a significantly longer fricative duration and a significantly shorter preceding vowel duration than /s/, a pair of results that run counter to general tendencies for voiced fricatives to be shorter and have longer preceding vowels than their voiceless counterparts. We propose that these durational findings may explain, at least in part, the salience of final /z/ devoicing in Latinx Englishes despite its ubiquity among speakers of mainstream US English. In this first instrumental sociophonetic account of final /z/ devoicing in Latinx Englishes, we also find that, counter to existing segmental accounts, the morphological status of /z/ is no longer a significant predictor of devoicing. Moreover, while both following segment and speaker gender are significant predictors of devoicing, they do not condition devoicing in the expected ways.